Reappraisal of the relationship between the HIV-1-protective single-nucleotide polymorphism 35 kilobases upstream of the HLA-C gene and surface HLA-C expression. - Corrah, T; Goonetilleke, N; Kopycinski, J; Deeks, S; Cohen, MS; Borrow, P; McMichael, A; Brackenridge, S (2011)
Previous studies have found an association between a single-nucleotide polymorphism 35 kb upstream of the HLA-C locus (-35 SNP), HLA-C expression, and HIV-1 set point viral loads. We show that the difference in HLA-C expression across -35 SNP genotypes can be attributed primarily to the very low expression of a single allelic product, HLA-Cw7, which is a common HLA type. We suggest that association of the -35 SNP and HIV-1 load manifests as a result of linkage disequilibrium of this polymorphism with both favorable and unfavorable HLA-C and -B alleles.